SARS-CoV-2 infection related mortality and comorbidities in a dedicated COVID-19 facility: A record based analysis from Uttar Pradesh - Gupta, Richa; Singh, Balvir; Gautam, Ashish; Singh, Geetu; Khan, Mausim; Kumar, Vikas (Asian Journal of Medical Sciences, 2022)
Background: In India, on 30th January 2020, the first case of COVID-19 was reported, thereafter country has faced two waves with disastrous second wave. A total of about 34 million cases and 4.68 lakh deaths have been reported so far from India. Few studies have reported death rate as 5.7% among COVID-19 patients with at least one co-existing medical condition, as compared to 0.7% in patients without any comorbidity. Aims and Objectives: We aim to analyze the death audit data of 467 COVID-19 death cases considering factors of age, gender, area of residence, cause of death, related comorbidities, and relation with duration of hospital stay and presence or absence of comorbidity in COVID-19 death cases. Materials and Methods: This is an observational study from April 2020 to July 2021which is based on records obtained from death audit reports of a dedicated COVID-19 facility at a tertiary hospital, Agra, Uttar Pradesh. The state authorities introduced a standard “COVID-19 Death Audit Proforma” on a death audit portal to audit all deaths related from COVID-19 (SARS-CoV-2) infection. Statistical analysis used: The data were recorded in Microsoft Excel and analyzed using statistical software, Microsoft Excel (Version 16.49). The results are presented accordingly in form of descriptive statistics. Results: We have reported findings from 467 COVID-19 deaths from our dedicated COVID-19 facility in the present study. Median age of deceased was found to be 57 years with (71.9%) deaths in males, with predominantly 77.1% of patients residing in urban area. 74% of COVID-19 deaths were reported along with one or more comorbid illness at the time of admission with hypertension to be the most common comorbid disease (42.9%) followed by diabetes (34.5%). Median length of hospital stay is reported as 4 days. Conclusion: Our analysis from Uttar Pradesh dedicated COVID-19 facility found that comorbidities were present invariably in 74% of deaths from SAR-CoV-2 infection. Early diagnosis and timely aggressive management is pillar for reducing morbidity and mortality from COVID-19 disease.